Research on Self-locking and Efficiency Maximization of 3K（Ⅲ） Type Planetary Gear Train Based on the Transmission Ratio Method - Xu Mengchong; Sun Wei; Yang Yifan; Kong Jianyi; Su Pincheng (Jixie chuandong)
The planetary gear train has compact structure, high transmission efficiency, and is widely used in industrial manufacturing. There is a wide application space for the planetary gear train of the self-locking mechanism. In this study, the power flow direction and efficiency formula of the 3K(Ⅲ) type planetary gear train are analyzed, and the operation performance is improved by optimizing the efficiency of this kind of planetary gear train when it is self-locking. Thus, the setting of the transmission ratio and the corresponding efficiency of the reverse self-locking planetary gear set with higher transmission efficiency can be obtained. Firstly, the transmission ratio of the epicyclic gear train is solved by using the basic formula. Secondly, the power flow direction of epicyclic gear trains is analyzed according to different conditions. Thirdly, the efficiency curve is drawn based on the above conditions and the transmission ratio of the self-locking gear train is analyzed with an example. Finally, through detailed case studies, the accuracy and efficacy of this approach are verified, providing the transmission ratio setting for maximizing the efficiency of the planetary gear train during reverse self-locking scenarios.